Exploring the biogeography, morphology, and phylogeny of the condylostomatid ciliates (Alveolata, Ciliophora, Heterotrichea), with establishment of four new Condylostoma species and a revision including redescriptions of five species found in China - Yong Chi; Fan Wei; Danxu Tang; Changjun Mu; Honggang Ma; Zhe Wang; Khaled A. S. Al-Rasheid; Hunter N. Hines; Xiangrui Chen (Marine Life Science & Technology, 2024)
Species of the ciliate class Heterotrichea Stein, 1859 are a cosmopolitan group of unicellular eukaryotic microorganisms, many of which have been widely used as models in various fields of research such as regenerative biology, functional ecology, environmental toxicology, and symbiotic behavior. However, species identification in the heterotrich family Condylostomatidae, especially the most species-rich and type genus Condylostoma Bory de Saint-Vincent, 1824, remains challenging due to incomplete original descriptions, few reliable distinguishing characters, and overlapping features between different species. This study presents an updated revision of Condylostoma and its related genus Condylostomides da Silva Neto, 1994 based on descriptions of five species, including nine populations collected from China, using both morphological and molecular methods. The main findings are as follows: (1) 43 nominal species and about 130 populations are reviewed, resulting in the recognition of 30 valid species of Condylostoma and eight valid species of Condylostomides ; (2) keys, synonyms, biogeographic distributions and amended/improved diagnoses of all valid species are provided; (3) based on the available data, four new Condylostoma species ( C. marinum sp. nov., C. petzi sp. nov., C. villeneuvei sp. nov., and C. microstomum sp. nov.), one new combination ( Condylostomides minimus (Dragesco, 1954) comb. nov. & nom. corr.), and two corrected names ( Condylostoma ancestrale Villeneuve-Brachon, 1940 nom. corr. and Condylostomides nigrus (Dragesco, 1960) nom. corr.) are suggested; (4) cryptic species are detected and proposed for the first time to form the Condylostoma curvum species complex; (5) three highly confusing Condylostoma species, C. kris , C. spatiosum , and C. minutum , are redefined for the first time based on modern taxonomic methods; (6) a ‘flagship’ species, Condylostomides coeruleus , is recorded for the first time from the continent of Asia, substantially expanding its biogeography; (7) ciliature adjacent to the distal end of the paroral membrane within the family Condylostomatidae is uniformly defined as frontal membranelles and is classified into three patterns according to the arrangement of kinetosomes, which serve as important key features.